In Their Own Words Forgotten Women Pilots of Early Aviation - Erisman, Fred (Purdue University Press, 2021)
Amelia Earhart's prominence in American aviation during the 1930s obscures a crucial point: she was but one of a closely knit community of women pilots. Although the women were well known in the profession and widely publicized in the press at the time, they are largely overlooked today. Like Earhart, they wrote extensively about aviation and women's causes, producing an absorbing record of the life of women fliers during the emergence and peak of the Golden Age of Aviation (1925-1940). Earhart and her contemporaries, however, were only the most recent in a long line of women pilots whose activities reached back to the earliest days of aviation. These women, too, wrote about aviation, speaking out for new and progressive technology and its potential for the advancement of the status of women. With those of their more recent counterparts, their writings form a long, sustained text that documents the maturation of the airplane, aviation, and women's growing desire for equality in American society.